Targeted arsenite-loaded magnetic multifunctional nanoparticles for treatment of hepatocellular carcinoma. (15th February 2019) - Chi, Xiaoqin; Zhang, Renyuan; Zhao, Tian; Gong, Xuanqing; Wei, Ruixue; Yin, Zhenyu; Lin, Hongyu; Li, Dan; Shan, Hong; Gao, Jinhao
Abstract: Arsenic trioxide (ATO), an FDA-approved drug for acute promyelocytic leukemia, also has great potential for treatment of solid tumors. Drug delivery powered by recent advances in nanotechnology has boosted the efficacy of many drugs, which is enlightening for applications of ATO in treating solid tumors. Herein, we reported arsenite-loaded multifunctional nanoparticles that are capable of pH-responsive ATO release for treating hepatocellular carcinoma (HCC) and real-time monitoring via magnetic resonance imaging. We fabricated these nanoparticles (designated as magnetic large-pore mesoporous silica nanoparticle (M-LPMSN)-NiAsO x ) by loading nanoparticulate ATO prodrugs (NiAsO x ) into the pores of large-pore mesoporous silica nanoparticles (LPMSNs) that contain magnetic iron oxide nanoparticles in the center. The surface of these nanodrugs was modified with a targeting ligand folic acid (FA) to further enhance the drug efficacy. Releasing profiles manifest the responsive discharging of arsenite in acidic environment. In vitro experiments with SMMC-7721 cells reveal that M-LPMSN-NiAsO x -FA nanodrugs have significantly higher cytotoxicity than traditional free ATO and induce more cell apoptosis. In vivo experiments with mice bearing H22 tumors further confirm the superior antitumor efficacy of M-LPMSN-NiAsO x -FA over traditional free ATO and demonstrate the outstanding imaging ability of M-LPMSN-NiAsO x -FA for real-time tumor monitoring. These targeted arsenite-loaded magnetic mesoporous silica nanoparticles integrating imaging and therapy hold great promise for treatment of HCC, indicating the auspicious potential of LPMSN-based nanoplatforms.